756. Clostridioides difficile Burden of Disease: A Prospective Population-Based Surveillance Study of Hospitalized Adults in Louisville, Kentucky. (4th December 2021) - Furmanek, Stephen; Carrico, Ruth; Angulo, Fredrick J; Zamparo, Joann; Gonzalez, Elisa; Ford, Kimbal D; Ramirez, Julio
Abstract: Background: Clostridioides difficile ( C. difficile ) is an important cause of morbidity and mortality. C. difficile infection (CDI) may be frequently under-diagnosed because laboratory confirmation requires collection of a stool specimen from a patient with diarrhea and appropriate laboratory testing. Methods: A prospective population-based CDI surveillance study was launched in 8 adult hospitals in Louisville, Kentucky on September 16, 2019. Surveillance officers in each hospital identified all cases of new-onset diarrhea (≥3 loose stools in the past but not preceding 24 hours) in Louisville residents ≥50 years of age. After informed consent, stool samples were collected and tested at the University of Louisville reference laboratory for 1) glutamate dehydrogenase (GDH) and 2) Clostridioides difficile toxins A and B using C. DIFF QUIK CHEK COMPLETE®, Techlab. We defined CDI as GDH positive and toxin positive. The study was paused on April 3, 2020, due to COVID-19 restrictions. Results: There were 85, 719 eligible patient-days during the study period. A total of 1541 patients had new-onset diarrhea corresponding to 1.8 cases of new-onset diarrhea per 100 eligible patient-days. We enrolled 84% (1291/1541) of patients with new-onset diarrhea and tested stool samples for C. difficile from 82% (1055/1291) for a testing density of 123 per 10, 000 patient-days. Of the 1055 tested stool specimens, 73 (7%) were GDH positive and toxin positive (Figure 1) yielding a hospital-based CDI incidence of 8.5 CDI cases per 10, 000 patient-days. Figure 1. Patient Ascertainment Flow Chart Conclusion: New-onset diarrhea was common among hospitalized adults ≥50 years of age. CDI was frequently identified through stool specimens collected from eligible inpatients with new-onset diarrhea. Further analysis of these data and additional laboratory testing will contribute to a better understanding of the frequency of CDI underdiagnosis and the burden of CDI in the United States. Disclosures: Ruth Carrico, PhD, DNP, APR, CIC, Pfizer (Consultant, Research Grant or Support, Speaker's Bureau)Sanofi Pasteur (Consultant, Grant/Research Support, Speaker's Bureau) Fredrick J. Angulo, DVM, PhD, Pfizer, Inc. (Employee) Joann Zamparo, MPH, Pfizer, Inc. (Employee) Elisa Gonzalez, MS, Pfizer, Inc. (Employee) Kimbal D. Ford, PharmD, Pfizer, Inc. (Employee) Julio Ramirez, M.D., FACP, Pfizer, Inc. (Scientific Research Study Investigator, Research Grant or Support, Speaker's Bureau)